KOORDINASIPENYELENGGARA PEMILIHAN UMUM PADA PILKADA 2015 DIKABUPATEN MAJENE - Rahmayani Rahmayani; Burhanuddin Burhanuddin; Andi Luhur Prianto (Kolaborasi : Jurnal Administrasi Publik, 2019)
The purpose of this research is to know the coordination of election executors of 2015 election in Majene Regency. This research type is qualitative descriptive which involved six informants.' The data was collected by using instrument of observation, and interview. The results of this study indicate that the informant responses about the role of election executors in the 2015 election have been well managed but they still have to improve the less effective part of the election, one of them is the lack of legal firmness for election organizers whose led to the practice of money politics, the election excecutors which apply injuridil applicable, sociologically applicable, and philosophically applicable.